Behavior of normal-strength recycled aggregate concrete filled steel tubes under combined loading. (1st January 2017) - Chen, Jie; Wang, Yuyin; Roeder, Charles W.; Ma, Ji
Highlights: Experiments on 51 RACFST beam-columns. Scatter of the behavior of RACFST beam-columns. Behavior of RACFST beam-columns with different RCA sources. Development of design recommendations for RACFST beam-columns. Comparison with current design provisions. Abstract: The use of recycled aggregate concrete (RAC) for the fill in concrete filled steel tube (CFST) members (RACFST members) is proposed as a practical structural application. An experimental study of RACFST members with normal-strength concrete under combined loading is summarized. Forty-eight columns and three beams in groups of 3 identical specimens were tested to failure. Study parameters included recycled coarse aggregate (RCA) replacement percentage, source of RCA, eccentricity, slenderness, and the steel to concrete area ratio. Experimental results are consistent with less than 3% scatter within each group. The maximum compressive load of the columns decreased modestly with increasing substitution level of RCA (up to 11.2%), and the structural effects of the recycled aggregate replacement on load capacity and initial stiffness are smaller than the corresponding changes in material properties. The source of RCA had little effect on the behavior of RACFST under combined loading for this test program, and the similar size grading and index of crushing obtained in the aggregates may have provided this benefit. These observations support the use of RACFST in structural engineering. Current CFST design provisions are compared to the RACFST test results, and the design recommendations for RACFSTs are presented.